From Streams to streaming: A critique of the influence of STEM on students’ imagination for a sustainable future (Journal of Applied Learning and Teaching, 2020)
This article provides a literature-based critical review of STEM (Science, Technology, Engineering and Mathematics) and STEM education. STEM is located in and contributes to a neoliberal view of economics and is narrowly focused on technological solutions to global problems. As such, it is unable to provide the kind of education students at all levels need for them to understand, imagine and prepare themselves for a sustainable future. The article calls for a reframing of science away from the technological focus of STEM, i.e. techno-science, towards a science of reconnection with nature and an opening of students’ imagination, and considers some of the elements of university leadership that are needed to enable this.